2018
DOI: 10.1016/j.bar.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

The impact of audit quality on real and accrual earnings management around IPOs

Abstract: This is a repository copy of The impact of audit quality on real and accrual earnings management around IPOs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(114 citation statements)
references
References 84 publications
5
105
2
2
Order By: Relevance
“…After the Revolution, the external auditors' remuneration has gone up leading to more discretionary space for managers to smooth their net income. Antle et al (2006) found this same result; they considered that the high remuneration of auditors deprives them of their independence, which facilitates the coalition of interests; this high remuneration can occur at the end of each financial year, as shown by Alhadab and Clacher (2018). It can be temporary for one year, specifically for new external auditors after the Revolution, and is called abnormal remuneration.…”
Section: Discussionmentioning
confidence: 81%
“…After the Revolution, the external auditors' remuneration has gone up leading to more discretionary space for managers to smooth their net income. Antle et al (2006) found this same result; they considered that the high remuneration of auditors deprives them of their independence, which facilitates the coalition of interests; this high remuneration can occur at the end of each financial year, as shown by Alhadab and Clacher (2018). It can be temporary for one year, specifically for new external auditors after the Revolution, and is called abnormal remuneration.…”
Section: Discussionmentioning
confidence: 81%
“…There exist studies where the real activities manipulation has been tested in other settings, not especially connected with initial public offerings (Graham et al 2005;Roychowdhury 2006;Cohen and Zarowin 2010;Kothari et al 2016). Earnings management through real activities around IPO has been discussed in a limited setting so far (Alhadab and Clacher 2018;Wongsunwai 2013). This study could also be continued by analyzing the trade-off decision between real and accrual-based earnings manipulation (Zang 2012;Kothari et al 2016).…”
Section: Discussion Of Empirical Results and Future Researchmentioning
confidence: 99%
“…The characteristics of the audit committee have a positive role on the firm value significantly (Afza and Nazir, 2014). One of the audit functions as a controller, Audit Quality can overcome earnings management actions by companies in manipulating information (Alhadab & Clacher, 2018;Alzoubi, 2018;Muttakin et al, 2017;Alzoubi, 2016;Huguet & Gandia, 2016;Zgarni et al, 2016;Rusmin et al, 2014;Lin et al, 2012;Rusmin, 2010;Prawitt et al, 2009). So the hypothesis of this study is: Hipotesis 4.…”
Section: Hypothesis Development 221 Earnings Management Influence Omentioning
confidence: 94%
“…At this stage, the role of auditors is necessary for investors to get their rights in receiving financial information company (Almutairi et al, 2009). By functioning as a controller, auditor qualified to suppress acts of earnings management by the company (Alhadab & Clacher, 2018;Asthana, 2014;Prawitt et al, 2009;Alzoubi, 2016;Huguet & Gandia, 2016;Rusmin, 2010;Rusmin et al, 2014;Zgarni et al, 2016) are also tax planning actions (Lin et al, 2012) resulting in the quality of financial statements (Alzoubi, 2018) according to regulations (Bepari, 2015) and have a good impact on performance (Hua et al, 2016) and firm value (Afza, 2014;Houmes et al, 2013;Khan et al, 2016),…”
Section: Introductionmentioning
confidence: 99%